Novel PtCo alloy nanoparticle decorated 2D g-C3N4 nanosheets with enhanced photocatalytic activity for H2 evolution under visible light irradiation. Issue 46 (20th October 2015) - Han, Changcun; Lu, Yan; Zhang, Junlong; Ge, Lei; Li, Yujing; Chen, Changfeng; Xin, Yongji; Wu, Linen; Fang, Siman
Abstract : Novel PtCo/g-C3 N4 nanosheets with efficient visible light induced photocatalytic activity for H2 evolution. Abstract : Novel two-dimensional (2D) graphitic carbon nitride (g-C3 N4 ) photocatalysts decorated with PtCo bimetallic alloy nanoparticles (NPs) were prepared via an in situ chemical deposition method. The physical and chemical properties of the as-prepared PtCo/g-C3 N4 samples were characterized by X-ray diffraction (XRD), ultraviolet-visible diffuse reflectance spectroscopy (DRS), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and surface photovoltage spectroscopy (SPV). The photocatalytic H2 evolution experiments indicate that the PtCo alloy co-catalyst can effectively promote the separation efficiency of photo-generated charge carriers in g-C3 N4, and consequently enhance the H2 evolution activity. The 1.0 wt% PtCo/g-C3 N4 nanosheet catalyst shows the highest catalytic activity, and the corresponding H2 evolution rate is 960 μmol h −1 g −1, which is enhanced 2.9 times compared to that of pristine bulk Pt/g-C3 N4 (330 μmol h −1 g −1 ) under visible light irradiation. The photocatalyst can keep stable and maintain catalytic activity after irradiation for 28 h. A possible photocatalytic mechanism of PtCo NPs on the enhancement of visible light performance is proposed to guide further improvement of other desirable functional materials.